Attitudes Toward Active Voluntary Euthanasia Among Community-Dwelling Older Subjects - Poli, Stefano (SAGE open, 2018)
The major extension of late-life expectancy has increased the significance of end-of-life issues, particularly among elderly people, considering both the role of medical practices in shaping and defining dying trajectories and the differences in national laws and in public attitudes about preservation of self-dignity and removal of pain in death. Avoiding a prolonged, painful, and undignified death provides for many a rationale for euthanasia. On the contrary, the fear of increased pressure to end one’s life prematurely and of potential abuses became often the main argument of opposition among vulnerable groups, like older people, especially when suffering from disability, chronic diseases, and lacking of autonomy. Through a representative cross-sectional survey, we studied 1,782 community-dwelling over-65s residents in Genoa (Italy), examining with bivariate and binary logistic regression analysis their attitudes toward active voluntary euthanasia (AVE), and exploring associations with sociodemographic characteristics, health and socioeconomic conditions, ideological orientations, and cultural practices. About 39.9% of our sample fully disagreed with AVE, 26.7% expressed tolerance, and 35.2% agreed completely. Results showed significant associations of different attitudes toward AVE with cultural values and moral practices, as well as with health and disability conditions, evidencing increasing full rejection toward AVE among over-75s profiles (46.3%). Our results suggest major intergenerational differences among older people, showing significant cultural change in attitudes toward end-of-life issues. If and to the extent that older age plays a role, it is rather still strongly associated with rejection than with acceptance of AVE.